Pemanfaatan Artificial Intelligence (AI) dalam Mendukung Pengembangan Soft Skill dan Kepribadian di Dunia Kerja - Diana Zumrotus Sa’adah; Farhan Zaldi; Syahrul Ramadhan; Redial Naku Lanye; Dio Rizki Akbar; David Zhe Pratama (Jurnal Bisnis Kreatif dan Inovatif, 2025)
The utilization of Artificial Intelligence (AI) in the workplace has expanded rapidly, focusing not only on improving efficiency but also on strengthening human resource capacity. This review article aims to analyze the contribution of AI in supporting the development of soft skills and the formation of adaptive professional personalities. The method employed is a literature review of academic publications related to the use of AI in developing nontechnical competencies. The findings indicate that AI has been proven to enhance efficiency and productivity through the automation of routine tasks, faster data analysis, and more precise decision-making support. However, the success of AI implementation does not lie in replacing human roles but rather in harmonizing the functions of machine intelligence with the unique abilities of humans, such as empathy, intuition, creativity, and ethical reasoning. Human–AI collaboration emerges as a key approach to ensuring that technology remains human-centered, enabling digital transformation to proceed ethically, inclusively, and sustainably. Additional findings show that AI is capable of providing personalized learning, real-time feedback, and contextual simulations that effectively train communication, collaboration, problem-solving, creativity, and critical thinking skills. Human-centered AI integration also supports the development of professional personalities that are adaptive and responsive to change.